Glaucoma Publication Trends in Leading General Ophthalmology Journals During the Past Quarter Century: Where Are the Clinical Trials?. Issue 6 (June 2021) - Leshno, Ari; De Moraes, C. Gustavo; Mezad-Koursh, Daphna; Belkin, Michael; Singer, Reut; Jaber, Wasim; Barkana, Yaniv; Skaat, Alon
Abstract : Précis: During the past quarter century, the rate of glaucoma-related publication in general ophthalmology journals increased due to higher representation in "experimentally oriented" journals. The rate of glaucoma randomized controlled clinical trial (RCT) articles decreased during the same time period. Purpose: To evaluate trends in rate of glaucoma publications in leading general ophthalmology journals over the past quarter century. Materials and Methods: Q1 ophthalmology journals Web sites were reviewed. Only journals not limited to certain subspecialty were considered "general" and included in the analysis. In addition we categorized journals orientation as either "clinical" or "experimental." The PubMed search engine was used to collect publications from the selected journals between January 1, 1995 to December 31, 2019. Publications captured by "glaucoma" or "ocular hypertension" filters were considered glaucoma related. The fraction of glaucoma articles out of total number of articles within each year for each journal was calculated. A linear mixed effects model was applied to detect trends in glaucoma publication rates during the study period. Results: Eight journals were included: 4 "clinically oriented" and 4 "experimentally oriented." The PubMed search yielded 72, 750 publications, of which 9329 (12.8%) considered "glaucoma related." Percentage of glaucoma publications remained stable within "clinically oriented" journals, and significantly increased within "experimentally oriented" journals (annual change of 0.3%, P <0.001). The number of glaucoma-related RCTs decreased significantly in each (annual change of −0.21% and −0.13%, respectively, P <0.05). Conclusions: There has been a significant rise in the rates of glaucoma publications in "experimentally oriented" journals, while their representation in "clinically oriented" journals remained stable over the past quarter century. This change might be due to the increasing efforts to develop more advanced methods for evaluation and treatment in glaucoma, although still unable to address clinical demands. The decrease in glaucoma-related RCT articles might indicate reduced funding for such research. Abstract : Supplemental Digital Content is available in the text.